Estimates of Heritabilities of Milk Fat and Milk Protein and Their Correlations with Milk Yield in Sahiwal Cattle of Punjab Pakistan - Baig, J. A.; Bilal, G.; Moaeen-ud-din, M.; Ulhaq, M.; Waheed, H. M.; Khan, M. S.; Qayyum, A.; Ahad, F.; Farooq, K.; Anwar, M. S.; Israr, T.; Akhtar, M.; Manan, A.; Qamar, M. I.; Gorsi, M. I.; Rehman, A.; Irfan, M.; Ahmed, F.; Haider, B. (Tropical Animal Science Journal, 2023)
This study aimed to estimate the genetic parameters for lactation milk yield (LMY), lactation fat yield (LFY), and lactation protein yield (LPY) in the Sahiwal cattle breed of Pakistan. Performance data of 3364 purebred Sahiwal cattle with 9964 herd test records were collected from the public and/or private herds. Various edits were applied, such as herd test day records < 3, unknown calving and drying dates, etc., which reduced the data set to 1039 animals with 4489 herd test records. Lactation yields for milk, fat, and protein were calculated using the test interval method. Preliminary data analysis was performed using PROC MIXED in SAS. The animal model under the REML method was used to estimate the genetic parameters of the milk yield, milk fat, and milk protein. A multivariate model (3-traits) was fitted, which included the fixed effects of parity besides random effects of herd-year-season of calving (HYS), animal and residuals for all three traits. Mean ± SD (kg) of LMY, LFY, and LPY were 1444.07±554.51, 60.48±25.18, and 48.26±19.39, respectively. Parity and HYS significantly varied (p<0.05) among cows for all investigated production traits. The estimates of heritabilities with their standard errors for LMY, LFY, and LPY were 0.164±0.065, 0.124±0.061, and 0.181±0.067, respectively. The phenotypic and genetic correlations were high among all three production traits, which ranged between 0.879 to 0.975 and 0.990 to 0.999, respectively, with standard errors ranging from 0.002 to 0.03. Low to moderate heritability estimates for milk component traits obtained in the present study suggest that these traits could be improved through genetic selection.